2011
DOI: 10.1017/s1368980011000358
|View full text |Cite
|
Sign up to set email alerts
|

The number of 24 h dietary recalls using the US Department of Agriculture's automated multiple-pass method required to estimate nutrient intake in overweight and obese adults

Abstract: Objective: To determine the number of 24 h dietary recalls required to adequately estimate nutrient intake in overweight and obese adults using the US Department of Agriculture's (USDA) automated multiple-pass method (AMPM). In addition, the study quantified sources of variation in dietary intake, such as day of the week, season, sequence of diet interviews (training effect), diet interviewer, body weight and within-and between-subject variances in the intake of selected nutrients. Design: Adults having a BMI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 26 publications
1
34
1
1
Order By: Relevance
“…However, it will be a concern with wider and more diversified cohorts. Indeed, considering that at least 3 non-consecutive days of 24-h recall are needed to represent typical intakes [33], the time commitment for participants could impact their motivation. Nevertheless, the web-based format of the R24W seems to be an important asset.…”
Section: Discussionmentioning
confidence: 99%
“…However, it will be a concern with wider and more diversified cohorts. Indeed, considering that at least 3 non-consecutive days of 24-h recall are needed to represent typical intakes [33], the time commitment for participants could impact their motivation. Nevertheless, the web-based format of the R24W seems to be an important asset.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the findings from the 24-h dietary recall procedure may not be representative of habitual eating behavior as only one measure was taken. The procedure would be more representative if conducted on at least three different occasions in line with previous research (Moshfegh et al, 2008; Epstein et al, 2011; Stote et al, 2011). Thirdly, participants' evening intake on Day 1 was assessed using dietary recall rather than being objectively measured under laboratory conditions, which may have an impact on the validity of these results.…”
Section: Discussionmentioning
confidence: 69%
“…Multiple administrations of 24-hour dietary recall in prospective studies that aim to determine change between points of time in mean usual intakes of groups are supported by national recommendations [50]. Recent evidence has shown that, for all food groups but the most rarely consumed, two to four dietary recalls were superior to use of Food Frequency Questionnaire data to estimate usual intake [51], and that obtaining 3 nonconsecutive days of 24-hour dietary recalls per month over a period of 6 months was adequate to estimate energy and macronutrient intakes [52]. The Web-based automated 24-hour dietary recall that will be used in this study was developed in French [53] based on the US Department of Agriculture Automated Multi-Pass Method [54] and validated among French-Canadian adults [55].…”
Section: Methodsmentioning
confidence: 99%